The relationship between adolescents’ instagram addiction levels and psychological needs - Üstündağ, Alev (Journal of Dependence, 2022)
Objective: Adolescents use social media applications. Instagram is one of these social media applications. For this reason, this research was conducted to determine whether there is a relationship between Instagram addictions and basic psychological needs of adolescents.Method: The research was carried out using the correlational method, one of the quantitative research methods. 198 adolescents between the ages of 12-15 participated in the study voluntarily. The data of the study were obtained by using the personal information form, the Instagram Addiction Scale, and the Basic Psychological Needs Scale.Results: The adolescents participating in the study spent a lot of time in front of the screen. Although the most used social media applications by adolescents are WhatsApp and Instagram, it has been observed that the level of Instagram addiction is below medium in the review. The level of basic psychological needs of adolescents is upper middle and there is a positive and significant relationship between Instagram addiction levels and basic psychological needs.Conclusion: the results of the Instagram Addiction Scale of adolescents differ according to age and screen use time and the results of the Basic Psychological Needs Scale also differed according to the grade level.
Keywords: Adolescent; Instagram; addiction; psychological needs